Free radical scavenging activity of Pterogyne nitens Tul. (Fabaceae) - Regasini, Luis Octávio [UNESP]; De Oliveira, Camila Martins [UNESP]; Vellosa, José Carlos Rebuglio [UNESP]; Oliveira, Olga Maria Mascarenhas De Faria [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Bolzani, Vanderlan Da Silva [UNESP] (My University, 2008)
As part of our ongoing research on antioxidant agents from Brazilian flora, twenty extracts and fractions obtained from Pterogyne nitens Tulasne (Fabaceae) were screened for free radical scavenging activity by using ABTS [2,2′-azinobis(3-ethylenebenzothiazoline-6-sulfonic acid)] and DPPH (2,2-diphenyl-1-picrylhydrazyl-hydrate) radicals colorimetric assay and β-carotene bleaching test. The strongest activity was found in ethyl acetate fraction from the stem barks, exhibiting IC50 values (in μg/ml) of 2.10 ± 0.1 and 10.2 ± 0.3 on ABTS•+ and DPPH•, respectively. Additionally, chromatographic fractionation of stem barks yielding myricetin, quercitrin and mirycetrin, three flavonols with remarkable antioxidant activity. © 2008 Academic Journals.
Keywords: ABTS; Antioxidant; Caesalpinioideae; DPPH; Fabaceae; Flavonoid; Flavonol; Free radical scavenging activity; Leguminosae; Pterogyne nitens